Optical study of colloidal quantum dots : toward efficient emission and lasing upon single- and multi-photon excitation - Wang, Yue (2015)
Colloidal quantum dots (CQDs) have become the research hotspot due to their exceptional merits including the facile emission spectral tunability by size and composition tailoring, the solution processibility, the broad absorption and the narrow emission spectra and so on. In this thesis, main efforts are devoted to explore the fundamental linear and nonlinear optical properties of CQDs and develop applications of CQD-based micro-lasers. The third-order nonlinear optical properties of heavy metal-free InP/ZnS CQDs have been comprehensively studied, which reveals that the InP/ZnS CQDs are potentially excellent fluorescent bio-probes under two-photon excitation. By rationally designing and employing the CdSe/CdS/ZnS core/shell/shell CQDs as the optical gain material, three-photon induced amplified spontaneous emission and lasing have been realized for the first time from CQDs. Record low threshold stimulated emission in blue spectral range have been achieved from the ternary alloy CdZnS/ZnS core/shell CQDs thanks to the intrinsic slow nonradiative Auger recombination. To solve the “green gap” challenge experienced in epitaxial semiconductor lasers, the optical gain properties of the green-emitting quaternary alloy CdZnSeS/ZnS core/shell has been comprehensively investigated for the first time, and ultra-low threshold stimulated emission in green region has been observed. Furthermore, low threshold whispering gallery mode lasers in blue and green regime under quasi-continuous wave pumping have been produced leveraging on CdZnS/ZnS and CdZnSeS/ZnS CQDs, respectively. Our results represent a great progress in the development of CQD-based lasers and hold strong potential in wide range of field in biology and photonics and their interaction of biophotonics.